Optimizing the solvent extraction process for high-value compounds from sweet cherry press cake treated with pulsed electric fields using response surface methodology - Rrucaj, Ervehe; Carpentieri, Serena; Siano, Francesco; Ferrari, Giovanna; Pataro, Gianpiero (Frontiers in Food Science and Technology, 2023)
Introduction: Cherry juice production generates substantial cherry processing by-products, presenting a significant environmental challenge. The valorization of these by-products can not only reduce management costs but also enhance profitability by recovering valuable intracellular compounds. Methods: This study aimed at the extraction of bioactive compounds with potent antioxidant activity from sweet cherry press cake using Pulsed Electric Fields (PEF)-assisted extraction. PEF pre-treatment, carried out using a predetermined field strength (E = 3 kV/cm) and total specific energy input (WT = 10 kJ/kg), was applied to the cherry press cake prior to the subsequent solid-liquid extraction (SLE) stage. To optimize the SLE process for both untreated and PEF-treated samples, Response Surface Methodology (RSM) was employed to determine the most effective extraction parameters, including extraction temperature (20–50°C), solvent concentration (0–50% ethanol in water), solid-liquid ratio (0.05–0.2 g/mL), and diffusion time (30–360 min). The objective was to maximize key response variables: total phenolic content (TPC), flavonoid content (FC), total anthocyanin content (TAC), and antioxidant activity (FRAP). The extracts obtained from both untreated and PEF-treated samples under optimal conditions underwent HPLC-DAD analysis. Results and discussion: The results revealed that, under optimized SLE conditions (50°C, 50% ethanol-water mixture, 0.2 g/mL solid-liquid ratio, and 360 min extraction time), PEF pre-treatment significantly enhanced the extractability of high-value compounds. This resulted in notable increases in TPC (+26%), FC (+27%), TAC (+42%), and antioxidant activity (+44%) compared to conventional SLE. Additionally, the application of PEF reduced extraction time (by 5–18 min) and solvent usage (by 2%). HPLC analysis identified cyanidin-3-O-rutinoside as the predominant phenolic compound in both untreated and PEF-treated extracts, with a remarkable increase (+2.3-fold) after PEF application. These findings underscore the potential of PEF-assisted extraction as a promising approach to maximize the recovery of valuable compounds from sweet cherry press cake, contributing to food waste reduction and enhanced value generation from by-products.